Small micro and medium entreprise empowerment strategy through stakeholder involvement to increase the performance - Sri Harini; Erni Yuningsih; Susi Hambany (STIE Binaniaga, 2019)
The purpose of the research is to identify and mapping of Micro Small and Medium Enterprises (MSMEs) condition in Bogor area, also to recommendation the policy and empowerment the policy of SMME through the stakeholder involvement, so it can be able to increase the MSMEs performance. The research’s object is MSMEs in Bogor area. It uses the SWOT analysis with the desk study research method that is collecting data or seconder information that relevant to the research activity and approach method survey that is collecting the data or primer information with in-depth interview method and Focus Group Discussion (FGD), and the parties relating to this research. Finding this research is value of IFAS score of 2.90 and the value of EFAS score of 2.55 then obtained Matric Internal-External (IE Matric). Based on the above conditions where the relative IFAS score above average and EFAS score medium, then strategy that can be applied to that position is stability strategy or growth through horizontal integration. Key-words: strategy, empowerment, and performance.